Gambaran Kebersyukuran Mahasiswa Perantau di Luar Negeri (Studi pada Mahasiswa Muslim Asal Indonesia yang Kuliah di Luar Negeri) - Maulida, Rika; Imadduddin, Imadduddin; Fadhila, Mahdia (Jurnal Al-Husna, 2022)
Gratitude is a form of one's acknowledgment of the existence of parties other than oneself who participate in the favors received, therefore gratitude can be a trait that is embedded in a person to always say thank you in response to what he has received. Based on the preliminary study conducted, it was found that gratitude is an important thing and needs to be present in the individual, especially for overseas students. Therefore, this study aims to find out how the image of gratitude for overseas students studying abroad and the factors that influence it. This research is a qualitative research with the type of phenomenology with the number of subjects as many as four people with the criteria that students from Indonesia who study in Muslim-majority countries and non-Muslim-majority countries, are at the strata one level or equivalent, are Muslim, unmarried, aged between 20 up to 25 years and willing to be a research subject. The data collection method used is semi-structured interviews and the provision of a supporting scale to the subject. The results of this study indicate that the picture of gratitude for overseas students who study abroad is based on seven aspects, namely intensity, frequency, span, density, knowledge, spiritual condition and deeds. Then for the factors that influence the gratitude of Muslim overseas students studying abroad are affective and welfare traits, prosocial traits, spiritual traits, have a broad view of life, have a positive perception of life, have good intentions towards something, a tendency to behave. Positive attitude is based on respect and good will and has a warm appreciation for others.